2011
DOI: 10.1108/02683941111112659
|View full text |Cite
|
Sign up to set email alerts
|

The role of star performers in software design teams

Abstract: Purpose This study seeks to extend previous research on experts with mainly ad hoc groups from laboratory research to a field setting. Specifically, this study aims to investigate experts' relative importance in team performance. Expertise is differentiated into two categories (task functions and team functions) and the paper aims to investigate whether experts in task and team functions predict team performance over and above the team's average expertise level. Design/methodology/approach Longitudinal, multi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 61 publications
0
24
0
1
Order By: Relevance
“…(), supported the idea that team properties (e.g., cultural diversity) are related to team outcomes (e.g., team creativity) through team information‐exchange activities. Volmer and Sonnentag's () empirical findings also supported that team diversity may increase the willingness of team members to seek the perspectives of other members, which in turn, enhance team performance. In particular, we found that team cultural diversity enhances individual creativity fully through employee information elaboration.…”
Section: Discussionmentioning
confidence: 88%
“…(), supported the idea that team properties (e.g., cultural diversity) are related to team outcomes (e.g., team creativity) through team information‐exchange activities. Volmer and Sonnentag's () empirical findings also supported that team diversity may increase the willingness of team members to seek the perspectives of other members, which in turn, enhance team performance. In particular, we found that team cultural diversity enhances individual creativity fully through employee information elaboration.…”
Section: Discussionmentioning
confidence: 88%
“…За высокопроизводительных работников, сверхпрофессионалов («звезд») идет конкуренция. В [Volmer, Sonnentag, 2011] утверждается, что вклад одного «звездного» программиста в результаты команды разработчиков программного обеспечения может быть выше совокупного вклада остальных членов команды. Ориентация компаний на сотрудников с выдающимися способностями и трудовыми показателями заведомо сужает поле поиска, что, в свою очередь, способствует ужесточению конкуренции за один и тот же пул талантов.…”
Section: практики управления талантамиunclassified
“…Where previous definitions of team effectiveness focused on team performance, member's attitudes and behaviors, Volmer and Sonnentag (2011) conceptualized team effectiveness as the combination of team and task functions. Here, the team functions are the facilitating interaction patterns amongst the members, for e.g.…”
Section: Literature Reviewmentioning
confidence: 99%